Marketing innovation influences on market and customer related performances: Evidences of Korean manufacturing companies - Tong-Keun Lee; Cheon Yu; Xiaoxu Dong; Yun Seop Hwang (Global Business & Finance Review (GBFR), 2016)
The marketing related literatures emphasize the key role of marketing for companies performances. However, not much attention has been paid to marketing innovations and their performances. Focusing on 2,149 Korean manufacturing companies, this paper examines the factors that influence companies' marketing innovation decisions and marketing performances by using the Heckman selection model for addressing the sample bias problem. Three key findings have been derived. First, by categorizing market orientation among the three components-customer orientation, competitor orientation, inter-functional coordination, the findings show that customer orientation enhances marketing performance, but does not influence marketing innovation decision. On the other hand, both competitor orientation and inter-functional coordination have positive influences on the marketing innovation decision, but not on marketing performance. Second, marketing innovation activities such as product design, promotion, placement, and price help to enhance marketing performance. Third, the factors that influence marketing innovation decision and their performance are different depending on technological level of an industry. The results suggest that the marketing related activities are more important in high-tech rather than in low-tech industries.
Keywords: 650; Marketing Innovation; Market Orientation; Innovative Capabilities; Government Support; Marketing Performance; Heckman Selection Model